2005
DOI: 10.1111/j.1440-1827.2005.01872.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of bronchioloalveolar carcinoma in donor lung after lung transplantation: Microsatellite analysis demonstrates a recipient origin

Abstract: Bronchioloalveolar carcinoma is a distinctive subtype of pulmonary adenocarcinoma, without effective therapy, although there have recently been some attempts to use lung transplantation. However, a high post-transplantation local recurrence rate is described with some controversy regarding the possible involved mechanisms, the main possibilities being the lymphatic spread and aerosolization. Presented herein is a case of a bilateral lung transplantation for a bilateral and pneumonic form of non-mucinous bronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…61,84,85 The observation that recurrence (which occurred in over half) was almost always confined to the (transplanted) lung [84][85][86][87] is both further evidence of the M A N U S C R I P T…”
Section: Biologic Behaviormentioning
confidence: 92%
“…61,84,85 The observation that recurrence (which occurred in over half) was almost always confined to the (transplanted) lung [84][85][86][87] is both further evidence of the M A N U S C R I P T…”
Section: Biologic Behaviormentioning
confidence: 92%
“…Microsatellite analysis of the lung specimens of the donor and the recipient have showed that recurrent tumours originated from the transplant recipient [30,65]. Since BAC is considered as a localised disease (and excluding possible tumoural contamination during the transplantation procedure), these observations suggest the existence of either extra-pulmonary tumoural stem cells that would remain dormant for several years [32], or of infectious agents with an extrapulmonary preclinical reservoir.…”
Section: Jsrv and Human Lung Cancermentioning
confidence: 97%
“…We have also performed a molecular analysis based in 15 tetranucleotide repeat loci that demonstrated the LCs had a molecular profile similar to the receptor, and in consequence their origin was outside the implanted donor lungs. This kind of method has been used in other reports to demonstrate the origin of cells in transplant biopsies . This profile discards the possibility that the donor implanted lungs had a PLCH undetected.…”
Section: Discussionmentioning
confidence: 94%